Pembelajaran Matematika Dengan Menggunakan Metode Penemuan Terbimbing Untuk Meningkatkan Kemampuan Penalaran Induktif Siswa SMP - Septiani, Nurul Intan; Solehudin, Sutresno (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2019)
This research is motivated by the low inductive reasoning ability of junior high school students. The purpose of this quasi-experimental study is to analyze: 1) whether the increase in the inductive reasoning ability of junior high school students whose learning uses the guided discovery method is better than students who have learned mathematics with expository methods, 2) students' responses to the application of the guided discovery method. Indicators of inductive reasoning ability measured in this study, namely: 1) determining the relationship between patterns for patterns of images or numbers, 2) estimating between those forming these patterns. The population in this study were all eighth grade students of SMP Negeri 44 Bandung. While the sample chosen was not random, but through a purposive technique based on the consideration of researchers and teachers, class VIII H was chosen as the experimental class and class VIII J as the control class. The subject that is used as teaching material is a circle. The instruments used were tests of inductive reasoning abilities, student questionnaires and observation sheets. Based on the analysis of all stages of the research it can be concluded that: 1) the increase in the inductive reasoning ability of junior high school students who obtain learning by using the guided discovery method is better than the increase in the inductive reasoning ability of junior high school students who obtain learning by using the expository method; 2) students give a positive response to learning by using the guided discovery method.